2018
DOI: 10.1212/nxi.0000000000000474
|View full text |Cite|
|
Sign up to set email alerts
|

Autoimmune septin-5 cerebellar ataxia

Abstract: ObjectiveTo report a form of autoimmune cerebellar ataxia in which antibodies target septin-5, a guanosine triphosphate (GTP)-binding neural protein involved in neurotransmitter exocytosis.MethodsArchived sera and CSF specimens with unclassified synaptic antibodies were re-evaluated by tissue-based indirect immunofluorescence assay. Autoantigens were identified by Western blot and mass spectrometry. Recombinant protein assays (Western blot, cell based, and protein screening array) confirmed antigen specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 10 publications
3
51
0
Order By: Relevance
“…4,5 Neurochondrin autoimmunity was previously described in 3 adult patients with cerebellar degeneration and in a child with chorea. 6,7 All but 1 of the 7 patients with clinical information available in our report had predominance of rhombencephalitis (cerebellar and brainstem localization). Myelopathy and acute psychosis (accompanying ataxia) and neuropathy (without other features) were each encountered in single patients.…”
mentioning
confidence: 58%
“…4,5 Neurochondrin autoimmunity was previously described in 3 adult patients with cerebellar degeneration and in a child with chorea. 6,7 All but 1 of the 7 patients with clinical information available in our report had predominance of rhombencephalitis (cerebellar and brainstem localization). Myelopathy and acute psychosis (accompanying ataxia) and neuropathy (without other features) were each encountered in single patients.…”
mentioning
confidence: 58%
“…Although one patient recovered spontaneously, one patient had a robust response to conventional rescue immunotherapy (plasma exchange, corticosteroids, IVIg), and one patient had transient improvement, with death following 6 months later. 156,157 Metabotropic Glutamate Receptor 1 Antibody mGLuR1 antibody is a biomarker of autoimmune cerebellar syndrome and has been classically reported in association with Hodgkin's lymphoma, although it has been reported in non-cancer-associated settings as well. The median age for symptom onset is 58 years (range: 33-81 years).…”
Section: Septin-5 Antibodymentioning
confidence: 99%
“…Third, the predominance of cerebellar ataxia deserves further investigations, given that septin-5 is expressed throughout the brain 10 and that human immunoglobulin G binds to most parts of the cerebellum and cerebrum. 2 It seems possible that heteromeric proteins with other septin family members might play a role here. 3 …”
mentioning
confidence: 99%
“…Over the past few years, neurology has witnessed an unprecedented discovery of new clinical entities related to autoantibodies targeting natively expressed neuronal proteins, often at the synapse. 1 In this issue of Neurology® : Neuroimmunology and Neuroinflammation, Honorat et al 2 report that they successfully dug for yet another disease. Starting with the observation in 6 patients of a specific, previously unknown antibody reaction with murine brain sections, the authors identified septin-5 as the underlying target of serum and CSF antibodies.…”
mentioning
confidence: 99%